The Calcium Channel α2δ1 Subunit: Interactional Targets in Primary Sensory Neurons and Role in Neuropathic Pain - Cui, Wenqiang; Wu, Hongyun; Yu, Xiaowen; Song, Ting; Xu, Xiangqing; Xu, Fei (Frontiers in Cellular Neuroscience, 2021)
Neuropathic pain is mainly triggered after nerve injury and associated with plasticity of the nociceptive pathway in primary sensory neurons. Currently, the treatment remains a challenge. In order to identify specific therapeutic targets, it is necessary to clarify the underlying mechanisms of neuropathic pain. It is well established that primary sensory neuron sensitization (peripheral sensitization) is one of the main components of neuropathic pain. Calcium channels act as key mediators in peripheral sensitization. As the target of gabapentin, the calcium channel subunit α2δ1 (Cavα2δ1) is a potential entry point in neuropathic pain research. Numerous studies have demonstrated that the upstream and downstream targets of Cavα2δ1 of the peripheral primary neurons, including thrombospondins (TSPs), N-methyl-D-aspartate receptors (NMDAR), TRPA1, TRPV1, and PKC, are involved in neuropathic pain. Thus, we reviewed and discussed the role of Cavα2δ1 and the associated signaling axis in neuropathic pain conditions.